2019
DOI: 10.1155/2019/3790728
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effects of Anthraquinones from Rhubarb in Central Nervous System Diseases

Abstract: Rhubarb is a well-known traditional Chinese medicine; it has been used in China for thousands of years. Rhubarb anthraquinones are the major medicinal ingredients derived from rhubarb including emodin, aloe-emodin, chrysophanol, rhein, physcion, and danthron. These different anthraquinone derivatives alone or in combination play a therapeutic role in central nervous system diseases (CNSD), such as cerebral ischemic stroke, intracerebral hemorrhage, traumatic brain injury, brain tumor, Alzheimer’s disease, depr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 78 publications
0
32
0
Order By: Relevance
“…Aloe‐emodin is a natural anthraquinone derivative, which is the active ingredient of traditional Chinese medicine (TCM), such as Cassia occidentalis , Polygonum multiflorum Thunb and Rheum palmatum L. [ 18‐20 ] Growing evidence showed that aloe‐emodin has many pharmacological effects, including anti‐inflammatory, [ 21 ] anticancer, [ 22 ] antibacterial [ 23 ] and neuroprotective [ 16 ] activities. Aloe‐emodin can significantly improve cognitive deficits in amnesia animal model induced by scopolamine, increase the activities of SOD, GPx activities and ACh content, and decrease the level of MDA and AChE activity in vivo .…”
Section: Quinones and Its Role In Admentioning
confidence: 99%
See 1 more Smart Citation
“…Aloe‐emodin is a natural anthraquinone derivative, which is the active ingredient of traditional Chinese medicine (TCM), such as Cassia occidentalis , Polygonum multiflorum Thunb and Rheum palmatum L. [ 18‐20 ] Growing evidence showed that aloe‐emodin has many pharmacological effects, including anti‐inflammatory, [ 21 ] anticancer, [ 22 ] antibacterial [ 23 ] and neuroprotective [ 16 ] activities. Aloe‐emodin can significantly improve cognitive deficits in amnesia animal model induced by scopolamine, increase the activities of SOD, GPx activities and ACh content, and decrease the level of MDA and AChE activity in vivo .…”
Section: Quinones and Its Role In Admentioning
confidence: 99%
“…Recent studies have found that anthraquinone derivatives from Rhubarb, including aloe‐emodin, chrysophanol, emodin, danthron, physcion and rhein, and play therapeutic roles in AD, cerebral ischaemic stroke, intracerebral haemorrhage, depression and others. [ 16,17 ] Quinones are the source of therapeutic substances from many Chinese medicines and have obvious effect on prevention and treatment of AD, which help in developing potent and safe drugs targeting NLRP3. In short, inhibiting the NLRP3 activity can be an attractive strategy for the treatment of AD.…”
Section: Introductionmentioning
confidence: 99%
“…The well-understood mechanisms of Emodin include its inhibition of different components of MAPK pathways and the inhibition of cell survival through inhibition of NF-κB family proteins. Moreover, its regulation of p38 MAPK, degradation of proteosomes, and inhibition of the PI3K-Akt pathway may also play a role in its neuroprotective activity [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Trichomonas vaginalis is the most common non-viral sexually transmitted human venereal disease that is most often detected in women and that does not appear to decrease with age, reaching a maximum rate in 48-to 51-year old women [25]. Tritrichomonas foetus protozoa strains cause the related sexually transmitted disease bovine trichomoniasis in cattle and pigs [26,27], and intestinal Interest in anthraquinones arises from the fact that they are reported to have multiple potential health benefits in cells and in vivo, including antibiotic [1,4,7,8], anticancer [2,[9][10][11], antidiabetic [4], antifungal [12], anti-inflammatory [13], anti-obesity [14], antioxidative [13,15], antiprotozoal [16][17][18], antiviral [19], cardioprotective [20], hepatoprotective [21], and neuroprotective [22] properties. Emodin and aloe-emodin are already widely used as stimulant laxatives sold in pharmacies to treat constipation [6,23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Interest in anthraquinones arises from the fact that they are reported to have multiple potential health benefits in cells and in vivo, including antibiotic [ 1 , 4 , 7 , 8 ], anticancer [ 2 , 9 , 10 , 11 ], antidiabetic [ 4 ], antifungal [ 12 ], anti-inflammatory [ 13 ], anti-obesity [ 14 ], antioxidative [ 13 , 15 ], antiprotozoal [ 16 , 17 , 18 ], antiviral [ 19 ], cardioprotective [ 20 ], hepatoprotective [ 21 ], and neuroprotective [ 22 ] properties. Emodin and aloe-emodin are already widely used as stimulant laxatives sold in pharmacies to treat constipation [ 6 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%